2005
DOI: 10.1017/s095026880500484x
|View full text |Cite
|
Sign up to set email alerts
|

Cellulitis incidence in a defined population

Abstract: A population-based insurance claims database was used to examine cellulitis incidence, anatomical sites of infection, complicating diagnoses, source of health service, and recurrence rates. Insurance claim files were searched for cellulitis ICD-9-CM codes 681.0-682.9. Complications of cellulitis including erysipelas, lymphadenitis, lymphangitis, and necrotizing fasciitis were also identified by ICD-9-CM codes. We found a cellulitis incidence rate of 24.6/1000 person-years, with a higher incidence among males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
175
4
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(201 citation statements)
references
References 9 publications
15
175
4
7
Order By: Relevance
“…17 The prevalence of foot ulcers in the late 50's might be due to the occurrence of neuropathy, vasculopathy and altered immune responses in diabetic individuals and they are more evident in the later age groups as the disease progress. 18 The present study showed male preponderance with 81 males & 22 females. Male preponderance in the present study could be explained on the basis that the males spend more time working outdoors, exposing their foot to more traumas.…”
Section: Discussionsupporting
confidence: 55%
“…17 The prevalence of foot ulcers in the late 50's might be due to the occurrence of neuropathy, vasculopathy and altered immune responses in diabetic individuals and they are more evident in the later age groups as the disease progress. 18 The present study showed male preponderance with 81 males & 22 females. Male preponderance in the present study could be explained on the basis that the males spend more time working outdoors, exposing their foot to more traumas.…”
Section: Discussionsupporting
confidence: 55%
“…The study population was similar to that described in literature with a predominance of older people and men. 3,11,12 The clinical presentations were also classical with diabetes mellitus as a major risk factor. 4,[13][14][15][16] Most of the patients received Inj crystalline penicillin and cloxacillin for Streptococci and Staphylococci.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of HIVassociated NF incidence being 14 hospitalizations per 100,000 personyears support the proposed increased risk of NF in HIV-infected patients, markedly above that reported in the general population. A commonly cited multistate incidence estimate of NF in the United States (US) is 4 per 100,000, based on a report by Ellis Simonsen and colleagues [19] using administrative data from 1997-2002. A markedly lower incidence of NF was found by Mulla et al in another population study, using similar approach, with NF reported in 1.3 per 100,000 hospital discharges in Florida in 2001 [20].…”
Section: Discussionmentioning
confidence: 99%